(untitled) (Research, Society and Development, 2021)
Objective: The aim was to analyze the prevalence of alcohol consumption among medical students at a private university in a city in the interior of Maranhão. Methodology: This is an exploratory research, with a quantitative approach, occurred with 47 (forty-seven) participants. The data collection occurred in the period from September to October 2021, through the questionnaire indexed in Microsoft Forms, the data were organized according to questionnaire prepared, used the programs Microsoft Office Excel 2019 and Microsoft Office Word 2016. Results and discussion: The study showed sociodemographic data as female corresponding in 66%, being the predominant age of over 30 years in 43%. The reasons that surrounded for consumption of alcoholic beverage mostly presented to keep up with the group. About the beverage they drink most often, beer was denoted in 75%. Finally, whether the academics considered that college increased their drinking habits was not 72% but 28%. As these results show, the motivations for the individual to enter into alcoholic states are diverse, some related to common sense are easy to be cited, such as curiosity and the influence of friends and/or parents, besides noting that there is an exacerbated consumption led even to a state of unconsciousness, being a preponderant factor for accidents, diseases and death. Conclusions: It is concluded that it is necessary that there are means of awareness, aimed at risk prevention, especially at the university itself, where these students are.